The Evolutionary Process Leading Up to the Anthropocene as Seen Through Pierre Teilhard de Chardin’s Cosmic Christology - Florio, Lucio (2023)
Fil: Florio, Lucio. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras. Departamento de Filosofía; Argentina